Navigating inclusion: understanding social perception, educational opportunity, and challenges for neurodiverse students in Bangladeshi formal education - Chowdhury, Sabbir Ahmed; Islam, Mohammad Ashraful; Nishat, Md. Tahmid Anjum; Nadiv, Md. Adnan; Ormi, Nosrat Jahan (Frontiers in Education, 2024)
Neurodiversity movement around the world pushes the society to ensure inclusion in all settings in where societal perspectives play the vital roles for effective changes. The aim of this study was to explore the scenario of inclusion of neurodiverse students of Bangladesh. This qualitative study sheds light on social perspectives toward neurodiverse students; as well as their educational opportunity and challenges in formal education. Through purposive sampling, eight parents of neurodiverse students and eight special educators were chosen as the sample of this study. In depth data were collected through interview questionnaire from both groups. Interpretation of data exhibited the misconception, prejudices, and social stigma toward neurodiverse students. Findings of the study also revealed the challenges regarding education of neurodiverse students such as: inadequacy of resources, awareness, teachers training and infrastructure. The study concludes by proposing possible strategies such as: proper policy and curriculum development, capacity building and awareness raising to overcome those challenges.